(untitled) (Global Business Management Review (GBMR), 2022)
This study will examine relationship between Intellectual capital Disclosure and Companies’ Performances in Nigeria. The study will make use of annual reports (secondary data) of all companies listed in the Nigerian Stock Exchange. The relationships will be determined using intellectual capital drivers under a number of hypotheses with regression analysis indicating the direction of the relationship of the variables. Data collected will be analysed by SPSS 14 for easy computation and understanding of the results.